Increased thermal suitability elevates the risk of dengue transmission across the mid hills of Nepal - Bipin Kumar Acharya; Laxman Khanal; Meghnath Dhimal (PLoS ONE, 2025)
The burden of climate-sensitive, mosquito-borne diseases, including dengue, has significantly increased in recent years. Understanding the temporal and spatial variations of these diseases is essential for effectively controlling potential outbreaks. In this study, we utilized Moderate Resolution Imaging Spectroradiometer (MODIS) satellite land surface temperature (LST) data (MOD11A2) and a temperature-dependent mechanistic model (R0) to predict the monthly suitability for dengue transmission in Nepal from 2001 to 2020 for both mosquito vectors, Aedes aegypti and Ae. albopictus. We divided the study period into two episodes: 2001–2010, which we characterized as the period of dengue emergence, and 2011–2020, identified as the period of rapid expansion. We compared the thermal suitability across these two time periods. The results indicated that approximately half of Nepal is thermally suitable for dengue transmission for at least one month, with the maximum transmission risk lasting up to nine months each year, a trend that has more or less remained stable over the past 20 years. However, strong temporal dynamics were observed in the hilly regions and around major urban centers such as Kathmandu and Pokhara, where the length of thermal suitability extended up to six months for both vector species. Consequently, the population exposed to thermal suitability increased significantly on a monthly basis. Compared to the emergence period, the proportion of the population exposed to a suitable thermal environment for six months or longer each year increased by 18% for Ae. aegypti and 20% for Ae. albopictus. These findings provide evidence-based insights that could assist health authorities in the control and management of dengue in Nepal.